Early spontaneous recanalization following acute carotid occlusion - Szabo, Kristina; Kern, Rolf; Gass, Achim; Griebe, Martin; Lanczik, Oliver; Daffertshofer, Michael; Hennerici, Michael G. (Journal of neuroimaging, 2008)
BACKGROUND AND PURPOSE Occlusion of the internal carotid artery (ICA) and stroke may be the consequence of either local thrombosis due to atherosclerosis or massive embolism. Up to date, there are only few reports of subsequent recanalization. METHODS We report 12/76 cases of acute ICA occlusion leading to ischemic stroke, in which early recanalization was identified. Ultrasound and stroke MRI findings, therapeutic options, and outcome are described. RESULTS 10/12 patients showed an- or hypoechogenic morphology of occlusion. While in 7/12 cases complete recanalization was seen, in 5/12 patients partial recanalization with filiform flow (4) or residual high-grade stenosis (1) was detected. 10/12 patients had territorial or subcortical infarction, while two showed small cortical lesions only. In 7/12 cases, a potential cardiac source of embolism was found. Five patients received tPA; four patients underwent early carotid endarterectomy of the partially recanalized ICA within 48 hours. In the 10-day follow-up examination 10/12 patients showed clinical improvement as measured by the NIHSS. CONCLUSIONS Spontaneous recanalization after occlusion of the ICA may occur and might be more frequent than hitherto assumed. Echogenicity analysis and serial examinations of symptomatic ICA occlusion is useful for identifying a patient subgroup that might benefit from further therapy.
Gesehen am 26.03.2021